2014
DOI: 10.1016/j.mce.2014.06.001
|View full text |Cite
|
Sign up to set email alerts
|

FOXO1-dependent up-regulation of MAP kinase phosphatase 3 (MKP-3) mediates glucocorticoid-induced hepatic lipid accumulation in mice

Abstract: Long-term treatment with glucocorticoids (GCs) or dysregulation of endogenous GC levels induces a series of metabolic diseases, such as insulin resistance, obesity and type 2 diabetes. We previously showed that MAP kinase phosphatase-3 (MKP-3) plays an important role in glucose metabolism. The aim of this study is to investigate the role of MKP-3 in GC-induced metabolic disorders. Dexamethasone (Dex), a synthetic GC, increases MKP-3 protein expression both in cultured hepatoma cells and in the liver of lean mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 42 publications
1
19
0
Order By: Relevance
“…Furthermore, rats treated with dexamethasone [15] and corticosterone [10] for 5 or 10 consecutive days, respectively, also develop augmented lipolysis rate preferentially under basal condition. This dual effect of GCs on visceral fat (induction of adipogenesis and lipolysis) corroborates to the expansion of abdominal fat and to the increase of hepatic flux of lipids that may lead to hepatosteatosis [10,17] . For comprehensive reviews about the effects of GCs in the adipose tissue biology and the development of central obesity refers to [12,13] .…”
Section: Research Highlightsupporting
confidence: 56%
See 1 more Smart Citation
“…Furthermore, rats treated with dexamethasone [15] and corticosterone [10] for 5 or 10 consecutive days, respectively, also develop augmented lipolysis rate preferentially under basal condition. This dual effect of GCs on visceral fat (induction of adipogenesis and lipolysis) corroborates to the expansion of abdominal fat and to the increase of hepatic flux of lipids that may lead to hepatosteatosis [10,17] . For comprehensive reviews about the effects of GCs in the adipose tissue biology and the development of central obesity refers to [12,13] .…”
Section: Research Highlightsupporting
confidence: 56%
“…Studies performed in vitro (hepatocytes) and in vivo (lean mice) revealed that mitogen-activated protein (MAP) kinase phosphatase (MKP)-3 is a downstream component of dexamethasone effects [17] . In this study the authors demonstrated that several metabolic adverse effects caused by chronic GC treatment can be attributed to induction of MKP-3 expression and it was dependent on forkhead box protein O1 (FOXO1).…”
Section: Research Highlightmentioning
confidence: 99%
“…GCs, via FOXO1, increase the expression of MKP3. Mice lacking MKP3 are protected from some GC-related metabolic effects such as weight gain, increased adiposity, liver lipid accumulation and insulin resistance (93). In mice, an impairment of mitochondrial function has been related to increased epididymal adiposity after GC treatment (94).…”
Section: European Journal Of Endocrinologymentioning
confidence: 99%
“…Lack of 11BHSD1 decreases hepatic steatosis, but the extent of the contribution of 11BHSD1 expression and activity in the liver to the lipid accumulation is controversial (73,118,119). MKP3 deficiency has been shown to protect mice from GC-induced fatty liver (93).…”
Section: European Journal Of Endocrinologymentioning
confidence: 99%
“…Genetic ablation of Foxo1 in hypothalamus is known to enhance glucose uptake in gastrocnemius muscle [33]. Recent efforts have demonstrated that reducing the endogenous level of Foxo1 by knockdown approach abolished the elevation of MAPK phosphatase-3 (MKP-3), a factor known to induce transcriptional activation of gluconeogenic phosphoenolpyruvate carboxykinase (PEPCK) and glucose-6-phosphatase complex (G6pase) in dexamethasone-treated hepatoma cells [34,35]. Hepatic activation of mitogen-activated protein kinase (MAPK) by injection of mitogen-activated protein kinase kinase (MEK)-expressing adenovirus increased protein expression of MKP-3 and fasting blood glucose despite that reduced nuclear localization of Foxo1 was noted [36].…”
Section: Foxo1 As a Negative Regulator Of Glucose Utilization In The mentioning
confidence: 99%